Hepatic and intestinal CYP3A expression and activity in broilers. Issue 6 (18th January 2013) - Osselaere, A.; De Bock, L.; Eeckhaut, V.; De Backer, P.; Van Bocxlaer, J.; Boussery, K.; Croubels, S.
Abstract : Cytochrome P450 is involved in drug metabolism. Subfamily CYP3A shows a degree of similarity across different animal species. However, little information is available about its expression and activity in broiler chickens. A RT‐PCR method was developed for the quantification of CYP3A37 expression in the liver and small intestine of broilers. A higher expression in the jejunum was observed compared with that in the ileum. In the liver, a significantly lower expression compared with that in the jejunum was noticed. Thus, the role of the small bowel in drug metabolism cannot be neglected in broilers. CYP3A activity was studied in vitro using midazolam as a substrate. Two protocols for the preparation of intestinal microsomes were compared. Mincing of the tissues before ultracentrifugation seemed to be more appropriate than a protocol based on ethylenediaminetetra‐acetic acid separation. CYP3A activity revealed to be the highest in the duodenum with a decreasing trend towards the ileum. Activity in liver was comparable to duodenal activity.